Using peer assessment in teaching pharmacology for medical undergraduates - Thilanka Seneviratne; Wathsala Edirisingha; Wathsala Palpola (The Asia Pacific Scholar)
Introduction: Pharmacology, though challenging, is fundamental in medical practice, necessitating effective knowledge acquisition and retention for future application. This study aims to analyse student perceptions of the newly introduced teaching method, peer assessment, to enhance pharmacology teaching. Method: Eighty-six third-year medical students of the Faculty of Medicine, University of Peradeniya participated in the peer assessment. They were divided into two groups of 40-45 and a case scenario in pharmacology was given to answer. Three volunteers from each group presented the answers. Peers evaluated the answers using provided criteria and gave feedback. The teacher then facilitated discussions, highlighting key points. Assessors and assesses perceptions on the teaching learning method was assessed using questionnaire and focus group discussions (FGD). Results: The majority of students (n=64) (74.41%) enjoyed the task of assessing their peers. 80.23% (n=69) acknowledged the value of peer assessment for student engagement. However, 34.88% (n=30) mentioned that they did not feel they had the skills and knowledge to assess their peers. 17.43% (n=15) mentioned that they were reluctant to be critical of their peers. In the FGD students mentioned that in this student-centered learning method all students actively participated than the usual small group discussion sessions. They could compare peers’ knowledge with their own knowledge and preferred the teacher grading to be combined with peer grading. Conclusion: Peer assessment for enhancing pharmacology teaching was well received by the students. Also, students emphasise the importance of lecturer guidance and advocate for a combined assessment approach to improve engagement and learning outcomes.